Using an Online Platform to Administer the Single-Session Point Subtraction Aggression Paradigm: An Initial Examination of Feasibility and Validity. (January 2021) - Ellis, Jennifer D.; Grekin, Emily R.; Dekeyser, Donald; Partridge, Ty
Online platforms represent a cost-effective option for data collection; however, it is unclear whether online administration of certain kinds of tasks (e.g., behavioral measures of aggression) poses validity threats. The present study provided a preliminary examination of effort (as indexed by total number of presses), differential drop-out, and believability of an online version of the single-session point subtraction aggression paradigm (PSAP). Two subsamples of participants were recruited; a sample recruited through Amazon's Mechanical Turk ( n = 758) and an in-person undergraduate sample ( n = 88). All participants completed the PSAP, along with measures of trait hostility and state anger. The online sample did not differ from the in-person sample on effort (i.e., total number of presses), and did not find the task less believable. Higher scores on state anger were associated with lower likelihood of beginning the online PSAP, but were not associated with prematurely closing the task. State anger was related to aggressive responding on the PSAP. Limitations of the online PSAP and considerations for future research are discussed.